1996
DOI: 10.3109/02713689609017628
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins increase proMMP-1 and proMMP-3 secretion by human ciliary smooth muscle cells

Abstract: These results suggest that induction of MMPs in situ following topical PG treatment may degrade ciliary muscle extracellular matrix and possibly contribute to increased uveoscleral outflow, as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
0
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(77 citation statements)
references
References 31 publications
1
73
0
3
Order By: Relevance
“…Their earlier work had shown that following treatment of human ciliary muscle cells in culture with PGF 2α , collagens type I and III were reduced while matrix metalloproteinases 1, 2, 3 and 9 were increased (Lindsey et al, 1996;Lindsey et al, 1997). In vivo, following topical treatment of monkey eyes for 5 days with PGF 2α , collagen types I, III, and IV immunoreactivity in the ciliary muscle and adjacent sclera was reduced (Sagara et al, 1999) while matrix metalloproteinases 1, 2, and 3 were increased (Table 1) (Gaton et al, 2001;Weinreb et al, 2002).…”
Section: Prostaglandins and Enhancement Of Uveoscleral Outflowmentioning
confidence: 99%
“…Their earlier work had shown that following treatment of human ciliary muscle cells in culture with PGF 2α , collagens type I and III were reduced while matrix metalloproteinases 1, 2, 3 and 9 were increased (Lindsey et al, 1996;Lindsey et al, 1997). In vivo, following topical treatment of monkey eyes for 5 days with PGF 2α , collagen types I, III, and IV immunoreactivity in the ciliary muscle and adjacent sclera was reduced (Sagara et al, 1999) while matrix metalloproteinases 1, 2, and 3 were increased (Table 1) (Gaton et al, 2001;Weinreb et al, 2002).…”
Section: Prostaglandins and Enhancement Of Uveoscleral Outflowmentioning
confidence: 99%
“…PGE is involved in stimulating MMP production (Lindsey et al, 1996;Zeng et al, 1996;Shankavaram et al, 1997), stimulation of IL-8 and IL-10 production (Strassmann et al, 1994;Agro et al, 1996;Denison et al, 1999), antibody class switching in B cells (Phipps et al, 1991;Roper et al, 1990) and inhibition of IL-12 synthesis from activated monocytes (Kraan et al, 1995). All of these properties of PGE are consistent with the damping of any Th-1 (cellmediated) response within decidua, where a major source of PGE would be the trophoblast (Kelly et al, 1995).…”
Section: Prostaglandinsmentioning
confidence: 99%
“…9,11 In addition, a reduction in collagen types I, III, and IV in PGF 2␣ -treated human ciliary muscle cultures have been reported. 14 Further, a reduction in these collagens was observed in the ciliary muscle of inflamed monkey eyes previously treated with PGF 2␣ -IE, in which uveoscleral outflow was also increased.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] Although studies have shown that MMPs can alter conventional outflow facility in human and animal perfused eyes, 16,17 direct evidence that MMPs participate in the FPagonist-induced modulation of IOP remains to be determined.…”
mentioning
confidence: 99%